Association of Health Plans' Healthcare Effectiveness Data and Information Set (HEDIS) performance with outcomes of enrollees with diabetes - Harman, Jeffrey S; Scholle, Sarah Hudson; Ng, Judy H; Pawlson, L Gregory; Mardon, Russell E; Haffer, Samuel C Chris; Shih, Sarah; Bierman, Arlene S (Medical care, 2010)
Few quality of care evaluations examine the relationship between clinical processes and patient outcomes. To determine the association between health plan performance on Healthcare Effectiveness Data and Information Set (HEDIS) clinical processes and intermediate outcome measures and Health Outcomes Survey (HOS) self-reported physical and mental health scores among Medicare plan enrollees with diabetes. Secondary data analysis of 2002 HEDIS and 2001-2003 HOS data. This study focused on Medicare plan enrollees with self-reported diabetes (N = 8184). Plan-level HEDIS diabetes care measures for 2002 and longitudinal, patient-level 2001-2003 HOS physical and mental health outcomes scores. Hierarchical linear models estimated the relationship between plan HEDIS performance on diabetes process of care and intermediate outcome measures and 2-year changes in enrollee HOS physical and mental health scores. Each 10% point improvement in plan performance on HEDIS intermediate outcomes (ie, the proportion of well-controlled diabetes) was related to significant positive increase in the probability of being healthy as measured by both enrollee physical health scores (7 percentage point increase, P < 0.05) and mental health scores (11 percentage point increase, P < 0.01). Similar increases in plan process of care measures were associated with increases in the probability of being healthy as measured by enrollee mental health scores (11 percentage point increase, P < 0.001). This study represents one of the first attempts to link plan HEDIS performance to changes in enrollee health. The results suggest that improved quality of care, as measured by process and intermediate outcomes measures for diabetes, can result in better health among patients with diabetes. Further research should address whether this relationship exists in other quality measures, clinical conditions, and populations.